Transformation of Human Resource Management to Increase Work Process Efficiency at Indonesian Quarantine Agency (A Study on The Implementation of Lean Management in Human Resource Management) - Suwarno Tri Widodo; Lijan Poltak Sinambela (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2025)
The field of Human Resource Management (HRM) in an organization aims to ensure that the organization achieves its established objectives by involving skilled and capable employees. One of the primary challenges faced is creating efficiency in work processes without compromising service quality. In the context of HRM, common issues include inadequate use of modern technology, complex procedures, resistance to change, and suboptimal interdepartmental collaboration. The transformation of HRM at the Indonesian Quarantine Agency through the application of lean management has become a strategic step to enhance work process efficiency and effectiveness. In this context, HRM plays a crucial role in achieving organizational goals by engaging skilled and capable employees. However, challenges such as bureaucratic procedures, resistance to change, and insufficient use of technology remain prevalent. This research employs the Soft Systems Methodology (SSM) approach to identify problems and formulate solutions. The results show that lean management implementation can reduce waste, increase added value, and optimize workflows. Through AHP analysis, it was found that the commitment of top and middle management, along with active employee involvement, are key factors for the successful implementation of lean management. Additionally, proper training on the concepts and techniques of lean management is prioritized to ensure the success of this transformation. Consequently, this study provides strategic recommendations to enhance productivity and service quality at the Indonesian Quarantine Agency while contributing theoretically to the development of HRM in the public sector.